An investigation on total ozone over western Mediterranean - Monge-Sanz, B.M.; Casale, G.R.; Palmieri, S.; Siani, A.M. (Societa italiana di fisica, 2003)
During recent years ozone depletion has been detected not only over polar regions but also over mid-latitude areas. This study analyzed daily total ozone (TO) data from three south-western European locations in order to detect long-time TO trends by means of a filtering technique. Correlation analysis with atmospheric circulation patterns was carried out to explain the decreasing trends observed. Results appear to show a strong correlation between TO decrease and the North Atlantic Oscillation and Arctic Oscillation Indices throughout recent decades. On the other hand, the trends also indicate that, at least during the last ten years, TO variations cannot be explained solely by natural atmospheric cycles over the studied area.